An Extensive Reading Approach to Language Teaching - Karapetyan, Lili (Armenian Folia Anglistika, 2008)
Reading, together with its various expressions, holds a leading position in foreign language teaching programs due to its huge educational significance. The article studies the role of extensive reading in language teaching, the ways of its application as well as its contribution to language teaching as a whole. Research suggests that extensive reading not only contributes to the improvement of reading skills of students, but also enriches their vocabulary and helps them perceive the new meanings of the already familiar words more easily.